Rancang Bangun Bak Mandi Bayi Otomatis Menggunakan Logika Fuzzy - Ardhana, Aliya Mitha; Wijayanto, Ardik; Rosalinda, Hanny Megawati; Gusti, Agrippina Waya Rahmaning (Elektron : Jurnal Ilmiah, 2024)
The temperature and the depth of water should be monitored during the process of bathing a baby. The acceptable temperature range for a baby's skin is very narrow, yet caregivers often pour water based on subjective estimation. Moreover, there are frequent cases of drowning during baby-bathing processes. This research aims to develop an automatic baby bathtub to facilitate safety and efficiency, by giving appropriate values of temperature and depth. The method used to control the temperature using fuzzy logic with two inputs: water temperature and depth. Meanwhile, the depth is controlled by a servo motor connected to a valve. Using fuzzy logic, Pulse-Width Modulation (PWM) signals—connected to the water heater, can be controlled so that the water reaches the desired temperature. Simulation implementation results show a similarity value of 99.72%, indicating the device accurately reads the temperature and the depth. Tests in real conditions show that the system functions well, with an average time of 2.99 minutes to increase the temperature by 2°C and 4.8 minutes for the valve to adjust the water depth.